AIR POLLUTION IN SURROUNDING ENVIRONMENT OF DOMESTI MINES – AMBIENT AIR AND PLANT DUST (Natural Resources and Technology, 2017)
The current and recent activities in the lead-zinc Sasa mine or copper Bucim mine and flotation of galena and sphaleriteor chalcopyrite, producing metals for market, are reason for possible troubles from tailing dam-pond and surrounding river,ambient air and plant dust. This appearance is significant for the surrounding environment, but legislative and ecological lawdirective limited the quantity of these. In this paper will be present results of investigations from plant (flotation), crushing andgrinding section, ambient around the mine etc. with quality of ambient air and presence of dust in the environment usingappropriate apparatus for these measurements.